Crystal templating through liquid–liquid phase separation. Issue 6 (3rd December 2014) - Mosses, Joanna; Turton, David A.; Lue, Leo; Sefcik, Jan; Wynne, Klaas
Abstract : Fluff-like crystal growth of water in 1, 2-dichloroethylene. Abstract : Controlled induction of crystal nucleation is a highly desirable but elusive goal. Attempts to speed up crystallization, such as high super saturation or working near a liquid–liquid critical point, always led to irregular and uncontrollable crystal growth. Here, we show that under highly nonequilibrium conditions of spinodal decomposition, water crystals grow as thin wires in a template-less formation of " Haareis ". This suggests that such nonequilibrium conditions may be employed more widely as mechanisms for crystal growth control.